«Ռոստամ Զալ» վէպի արուեստի համառօտ ակնարկ - Պողոսյան, Աննա (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
В отличие от иранского письменного героического романа, армянские версии которого создавались под влиянием устной передачи иранской традиции, были локализованы и национализированы устной обработкой, эпико-героическим характером, простым народным творчеством и языком, дошедшие до нас варианты, в основном, в прозе – повествовательной форме. Свободный прозаический размер сохранялся в некоторой степени, роман непрерывно передавался в устной форме, приобретая новые версии. Unlike the Iranian written heroic novel, the Armenian versions that were created under the influence of the oral transmission of the Iranian tradition, were localized and nationalized by oral processing, epic-heroic character, simple folk art and language. The versions that have come down to us are mainly in prose-narrative form, free prosaic format has been preserved to some extent. The novel has been continuously transmitted orally, acquiring new versions.
Keywords: Armenian church; Religion; Կրօնագիտութիւն